Perception and optics in the 16th century: some features of Della Porta’s theory of vision - Saito, Fumikazu (Circumscribere International Journal for the History of Science, 2010)
This article discusses introductorily some features related to the visual experience according to how the organ of sight was conceived of in the 16th century. For this purpose it presents the criticism raised by Giovambattista della Porta (1535-1615) against contemporary theories of vision as described in his treatise on optics entitled De refractione optices partem libri novem published in 1593. Analysis of Della Porta’s optics shows that such debate included the mathematical, physical, anatomical and physiological aspects of vision, defining thus a framework very much different from the one of modern optics